Oxidative Stress and Autophagy Are Important Processes in Post Ripeness and Brown Film Formation in Mycelium of Lentinula edodes - Tang, Lihua; Chu, Ting; Shang, Junjun; Yang, Ruiheng; Song, Chunyan; Bao, Dapeng; Tan, Qi; Jian, Huahua (Frontiers in Microbiology, 2022)
Lentinula edodes (Berk.) Pegler, the shiitake mushroom, is one of the most important mushrooms in the global mushroom industry. Although mycelium post ripeness and brown film (BF) formation are crucial for fruiting body initiation, the underlying molecular mechanisms of BF formation are largely unknown. In this study, proteomic quantification (relative and absolute) and metabolomic profiling of L. edodes were performed using isobaric tags and gas chromatography-mass spectroscopy, respectively. A total of 2,474 proteins were identified, which included 239 differentially expressed proteins. Notably, several proteins associated with autophagy were upregulated, including RPD3, TOR1, VAC8, VPS1, and VPS27. Transmission electron microscopy also indicated that autophagy occurred in post ripeness and BF formation. In time-dependent analysis of the metabolome, metabolites associated with oxidative stress and autophagy changed significantly, including mannitol, trehalose, myo-inositol, glucose, leucine, valine, glutamine, and 4-aminobutyric acid. Thus, oxidative stress and autophagy were important processes in post ripeness and BF formation in L. edodes, and new insights were gained into molecular mechanisms at proteome and metabolome levels.